BOEGERIELLA CONICA MENDOZA-PALMERO, MENDOZA-FRANCO, ACOSTA & SCHOLZ, 2019 (MONOGENOIDEA: DACTYLOGYRIDAE) PARASITIZING THE GILLS OF “LINCE CAT” PLATYNEMATICHTHYS NOTATUS (SILURIFORMES: PIMELODIDAE) COLLECTED IN IQUITOS, PERU - Murrieta-Morey, Germán Augusto (2021)
Platynematichthys notatus (Jardine, 1841), popularly known as "lince cat" stands out for being a very popular species in the ornamental fish market, being exported to different parts of the world. Despite its economic importance, the existing information on helminths that parasitize this species is very scarce. In this sense, the present study identified monogenoids that parasitize the gills of this fish. The gills of ten specimens of P. notatus from the commercial aquarium AQUATRADE SAC, placed in Iquitos-Peru were analyzed. After taxonomic identification, Boegeriella conica Mendoza-Palmero, Mendoza-Franco, Acosta & Scholz, 2019 was reported as the species that parasitizes the gills of P. notatus. The main morphological characteristics of the species are: a coiled tubular male copulatory organ forming approximately 2 1/2 rings, an accessory piece of a sigmoid shape, bars with anteriorly directed lateral projections. This species is mentioned for the second time parasitizing P. notatus. In addition, the results of this study indicate a high specificity between B. conica and its host P. notatus.